Costos de producción y su influencia en la rentabilidad del sector camaronero del cantón Balao en el periodo 2022. - Saraguro Muñoz, Geraldine Claudet; Campoverde Escalante, Diego Sebastian (Machala : Universidad Técnica de Machala, 2024)
A study was conducted on production costs and their influence on the profitability of the shrimp sector in Cantón Balao in 2022, considering the economic importance of this industry in Ecuador. The objective was to analyze production costs and their impact on the sector's profitability. A mixed-method approach with a positivist paradigm was employed, using interviews with accountants from five shrimp farms and analysis of financial ratios. The results revealed three main causes affecting cost distribution: outdated manual processes, inefficient supply chain management, and external factors such as price fluctuations and climatic events. Financial analysis showed a general trend towards reduced profitability, with some companies experiencing significant losses. It was concluded that there is a clear impact of production costs on the sector's profitability, evidenced by the decline in profitability indicators. Dependence on outdated systems and pressure from external factors eroded profit margins. Recommendations included the digitization of processes, the implementation of a unified supply chain management system, and the development of a comprehensive external risk management plan to improve the profitability and competitiveness of the shrimp sector in Balao.
Se realizó un estudio sobre los costos de producción y su influencia en la rentabilidad del sector camaronero del Cantón Balao en 2022, considerando la importancia económica de esta industria en Ecuador. El objetivo fue analizar los costos de producción y su impacto en la rentabilidad del sector. Se empleó un enfoque mixto con paradigma positivista, utilizando entrevistas a contadores de cinco camaroneras y análisis de ratios financieros. Los resultados revelaron tres causas principales que afectan la distribución de costos: procesos manuales obsoletos, gestión ineficiente de la cadena de suministro y factores externos como fluctuaciones de precios y eventos climáticos. El análisis financiero mostró una tendencia general hacia la reducción de la rentabilidad, con algunas empresas experimentando pérdidas significativas. Se concluyó que existe una clara afectación de los costos de producción en la rentabilidad del sector, evidenciada por la disminución en los indicadores de rentabilidad. La dependencia de sistemas anticuados y la presión de factores externos erosionaron los márgenes de ganancia. Se recomendó la digitalización de procesos, la implementación de un sistema unificado de gestión de la cadena de suministro y el desarrollo de un plan integral de gestión de riesgos externos para mejorar la rentabilidad y competitividad del sector camaronero en Balao.
Keywords: COSTOS; PRODUCCION; RENTABILIDAD; CAMARON